Sub-chronic Toxicological Evaluation of Drinking Water from Internally Displaced Persons (IDP) Camp in Wassa, Federal Capital Territory, Abuja, Nigeria - Adamu, Shehu Usman; Nasir, Suwaiba; Saliu, Oluremi A.; Idowu, Ayodeji O.; Edogbo, Blessing E.; Yisa, Abraham G.; Sada, Salima Adamu; Ebhodaghe, Frank Eromosele; Eya, Chukwunonso; Adams, Moses Dele; Tijjani, Habibu (Sahel Journal of Life Sciences FUDMA, 2024)
The number of Internally Displaced Persons (IDPs) camps has increased recently in Nigeria due to insurgency and natural disasters such as floods. This study aimed to evaluate the sub-chronic toxicological effects of the source of the drinking water in Wassa camp, Abuja, Nigeria. Forty-eight (48) mice were randomized into four (4) groups of twelve (12) mice each and orally administered different concentrations (5, 10, and 20 mL/kg body weight respectively) of the water sample from Wassa IDP for fourteen (14) days. The alteration was noticed in the liver and kidney indices of mice by a significant increase (p<0.05) in kidney-body weight ratio, kidney, liver and plasma protein concentrations, and a considerable decrease (p<0.05) in albumin, creatinine, uric acid and total bilirubin concentrations, 14-days post-treatment, particularly at a higher dose. Gamma-glutamyl transaminase in the liver and aspartate transaminase in both liver and kidney significantly (p<0.05) increased in mice with a resultant significant decrease (p<0.05) in the serum, 14 days post-treatment at 20 mL/kg bwt. There was no significant difference (p>0.05) observed in serum triglycerides, very-low-density-lipoprotein cholesterol concentrations at all doses 14-days post-treatment compared with the control but the concentrations of serum low-density-lipoprotein cholesterol and total cholesterol significantly reduced (p<0.05) at 20 mL/kg bwt 14-days post-treatment. The drinking water altered some liver-function indices while the cardiac-function indices were less affected. Therefore, prolonged consumption of the water may not be relatively safe. The provision of clean drinking water for the Wassa IDP camp will prevent adverse biochemical reaction reactions from prolonged water consumption.